Self Management terhadap Psychosocial Adjustment Pasien Penyakit Ginjal Kronis dengan Hemodialisa - Astuti Dwi (Department of Nursing Universitas Jenderal Soedirman, 2017)
Background: Patients with chronic kidney disease have physical limitations due to chronic pain and they should take regular hemodialysis therapy. The main cause of the deterioration of the psychosocial state of the patients undergoing hemodialysis is the failure to adapt to the current state of illness. Objective: To investigate the effect of self-management (education and SEFT therapy) towards psychosocial adjustment in patients with chronic kidney disease undergoing hemodialysis. Research Method: The method used is quasi experiment. The design used was pre-test and post-test with control group design. This study used purposive sampling with 32 patients with chronic kidney disease. The treatment provided is self-management with education and SEFT therapy in patients with chronic kidney disease during hemodialysis therapy at the hospital. The data collection used is questionnaire Pasychosocial Adjustment to Illness Scale (PAIS). Result of research: showed that the ability of psychosocial adjustment patients on pre-test had mean value (x̄) PAIS: 103,12 to increase in post test with mean value (x̄) PAIS: 141,81. Based on the results of wilcoxon test obtained p value 0,000, therefore p value <0.05, the hypothesis of this study is accepted. Conclusions and recommendations: The ability of psychosocial adjustment of patients increases after participating educational treatment and SEFT therapy. The engagement between patient, family and nurse during the education period and SEFT therapy can improve the patient's psychosocial adjustment as respond the changes in health status.